DESIGN EDUCATION AS A MEDIA TRANSMISSION OF SOCIAL VALUES BASED ON LOCAL WISDOM - Irfan Arifin; Muhammad Muhaemin; Satriadi Satriadi (Program Studi PGSD Universitas Flores, 2025)
Design education in the context of formal education is often limited to aesthetic achievement, ignoring its potential as a medium for forming social values. This study aims to (1) analyze the gap between the theoretical potential of design as a tool for social change and existing pedagogical practices and (2) propose a design education model based on local historical narratives as a transformative solution. Through a literature review method with library studies and reflective analysis of curriculum practices, the study developed a three-stage approach: (a) exploration of local historical sources (e.g., Makassar-Aboriginal relations), (b) reflection of social values in the narrative, and (c) creative translation in design projects. The findings show that this model develops technical competence and significantly strengthens students' multicultural awareness, historical empathy, and social responsibility. This study proves how integrating critical pedagogy, participatory design practices, and local wisdom can transform design education from merely teaching skills to becoming a vehicle for character formation. The study's implications recommend reorientating curriculum design based on values and socio-cultural contexts to create more relevant and transformative educational practices.